The crisis intervention model in social work: a narrative review of theory and practice - Dughi, Tiberiu (Technium Social Sciences Journal, 2025)
At the core of social work, crisis intervention provides people experiencing extreme pain, trauma, or societal crises immediate support. Social workers are especially important in helping people to stabilize themselves and link them to long-term resources whether they are reacting to mental health crises, child welfare issues, domestic abuse, or major disasters. This review investigates the roots of crisis intervention, looking at its success in many contexts and also evaluating recent developments influencing the area. Digital and AI-driven crisis interventions have increased accessibility and efficiency in the fast changing environment of today so that experts may reach those in need via online platforms and automated support systems. These developments, meantime, also create moral conundrums about privacy, accessibility, and the possibility of depersonalized treatment. Social workers themselves also experience growing degrees of burnout at the same time, and issues regarding the long-term viability of crisis intervention strategies still exist. Stronger monitoring systems, ongoing professional development, and legislative investments guaranteeing crisis response stays both responsive and compassionate are desperately needed, this review emphasizes. Including crisis response into more general social work plans will help us to create a more efficient, ethical, and sustainable approach that not only offers quick relief but also promotes long-term resilience and empowerment for people in crisis.